Bone Grafts, Bone Substitutes and Regenerative Medicine Acceptance for the Management of Bone Defects Among French Population: Issues about Ethics, Religion or Fear?. (19th June 2019) - Offner, Damien; de Grado, Gabriel Fernandez; Meisels, Inès; Pijnenburg, Luc; Fioretti, Florence; Benkirane-Jessel, Nadia; Musset, Anne-Marie
Several techniques exist to manage bone defects in patients: bone grafts (autograft, allograft, xenograft), use of synthetic bone substitutes, or use of the products of bone regenerative medicine. Studies generally focus on their efficacy, but few focus on their acceptance. Our objectives were to assess their theoretical acceptance among the French general population, and to identify issues justifying refusals, by mean of an open e-questionnaire. The questionnaire was submitted to a general French population, and explained these techniques in an understandable way. Participants were asked to say whether they would accept or refuse these techniques, specifying why in case of refusal (fear of the technique, ethical reasons, religious reasons). In total, 562 persons participated. Autograft and use of the products of bone regenerative medicine were the most accepted techniques (93.4% and 94.1%, respectively). Xenograft was the least accepted technique (58.2%). Most refusals were due to fear such as failure, pain, infection (autograft 8%, allograft 14.9%, xenograft 25.3%, synthetic bone substitutes 14.6%, and products of bone regenerative medicine 6.8%). Ethical reasons were mostly mentioned for allograft (6.4%) and xenograft (18.3%). Religious reasons were scarcely mentioned, only for xenograft (1.2%). Thus, acceptance of techniques does not seem to be greatly linked to sociodemographic characteristics in France. However, other countries with their own cultural, religious, and population patterns may show different levels of acceptance. This study shows that bone regenerative medicine is a promising research direction, reaching biological and also humanist quality standards, expected to improve the health of patients. Information is still the cornerstone to defuse issues about fear.